Analysis of the influence of assets, liabilities and equity on the profitability of Bank KB Bukopin Syariah 2019-2023 - Fauzan, Asrul; Hafizh, Muhammad (Geuthèë Institute, Aceh, 2024)
This research is expected to increase insight and knowledge regarding the influence of assets, liabilities and equity on profitability at Bank KB Bukopin Syariah in 2019-2023. In determining the sample in this research, the purposive sampling method was used. The device used in this research to process and analyze existing data is Eviews version 10 software. Research results show that assets have a significant effect on the profitability of Bank KB Bukopin Syariah in the short term, which means increasing assets are followed by increasing profitability. However, in the long term, assets do not have a significant effect on profitability. Liabilities have a significant effect on the profitability of Bank KB Bukopin Syariah in the short term. However, in the long term, liabilities do not have a significant effect on profitability. Equity has no effect on the profitability of Bank KB Bukopin Syariah in the short and long term. Assets, Liabilities and Equity simultaneously have a positive and significant effect on Profitability(Y) Bank KB Bukopin Syariah.